PEMBERDAYAAN EKONOMI LOKAL MELALUI PRODUK MOCHI NANAS DI DESA MANGGIS KECAMATAN NGANCAR - Lailatul Zuhriyah; Mitha Alviani; Atik Fauziah; Muhammad Aryachi Tajul Chudzaki (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
Local economic empowerment is a strategic approach to improving community welfare based on regional potential. This service aims to examine the utilization of pineapple in pineapple mochi products as a form of local food innovation that supports the strengthening of the community economy in Manggis Village, Ngancar, from August 08 to August 20, 2024. This activity was carried out using the PAR (Participation Action Research) method, starting with observations, in-depth interviews, and the economic impact on micro-entrepreneurs and the surrounding community. Pineapple mochi was chosen as an innovative product combining local wisdom, namely pineapple fruit, the village's superior commodity, with processing techniques and digital marketing strategies. The service results show that pineapple mochi products, as the main local ingredient, can increase new UMKMs for residents, increase the economic value of local commodities for farmers, and strengthen the identity of new pineapple culinary products in Manggis village, Ngancar.